Clinical evaluation of the effects of low-intensity laser (GaAlAs) on wound healing after gingivoplasty in humans Avaliação clínica dos efeitos do laser em baixa intensidade (GaAlAs) na cicatrização de gengivoplastia em humanos - Carla Andreotti Damante; Sebastião Luiz Aguiar Greghi; Adriana Campos Passanezi Sant'Ana; Euloir Passanezi (University of São Paulo, 2004)
Low-intensity laser therapy aims at pain suppression, edema reduction and acceleration of wound healing. The main goal of this study was to clinically evaluate the effects of Aluminum Gallium Arsenate laser - 670nm in wound healing after gingivoplasty in 11 patients. Surgery was performed in anterior superior and/or inferior regions. The right side of the patient (test group) received a laser energy density of 4J/cm², in a 48-hour interval, during one week, totalizing four sessions. The irradiation was punctual in a contact mode in three points. The left side did not receive irradiation (control group). Clinical evaluation was performed by five specialists in periodontology through photography of the treated areas at post-surgical periods of 7, 15, 21,30,60 days. The observers pointed the best healed side. The Sign test was used for statistical analysis with a confidence level of 5% (P<0.05). The examiners found a better pattern of healing sometimes in the test and sometimes in the control group until 21 days after surgery. After this period there was no apparent difference between them. There was no statistical difference between the sides (p>0.05). These results have shown that low-intensity laser therapy did not accelerate oral mucosa healing after gingivoplasty. A terapia com laser em baixa intensidade visa a biomodulação dos tecidos para se obter supressão da dor, redução do edema, e aceleração da cicatrização. O objetivo deste estudo foi avaliar, clinicamente, os efeitos do laser diodo de arseneto de gálio e alumínio (GaAlAs) - 670nm- na cicatrização de gengivoplastias em 11 pacientes. As cirurgias foram realizadas nas regiões anteriores superior e/ou inferior. O lado direito (teste) foi irradiado, na forma pontual, com 4J/cm² por ponto, em três locais diferentes. A aplicação do laser foi feita a cada 48h, durante uma semana, totalizando quatro sessões. O lado esquerdo (controle) não foi irradiado. A avaliação clínica foi feita por cinco periodontistas, através de fotografias dos períodos pós-operatórios de 7,15,21, 30 e 60 dias. Os examinadores apontaram o lado mais bem cicatrizado ou se ambos estavam iguais. Para análise estatística dos dados clínicos, foi utilizado o teste dos sinais com um nível de significância de 5% (p<0,05). Os resultados mostraram que havia preferência ora pelo lado teste, ora pelo lado controle até o período de 21 dias e nos períodos subseqüentes ambos os lados foram considerados iguais. A diferença entre os lados estudados não foi estatisticamente significante, sugerindo que o laser não acelerou a cicatrização da mucosa oral.